(untitled) (Sains Humanika, 2018)
The Fitrah creation refers to the origin of the event and the initial condition of the human being. It is a system created by Allah in every creature to determine the type of human being created from the aspect of the body and reason. This research had been carried out to identify the macrostructure of ayat a-Qur’an’ throughout human creation aspect. This research is a descriptive analysis using qualitative approach through document analysis technique. The data of the research stands from the entire two-way dialog that had been located inside the Qur’an. The analisys shows that ayat al-qur’an from human creation aspec is divided by two aspects, it is the origin of the human and humanity the humanity essence is prideful, tends toward truthfulness, love their races, the bond of their family and the need to be with each other. This showed that every human that had been created has this main essence of humanity that need to be put in check so that every approach that will be used in every field of life would take notice of all of the main essence that had been said in this paragraph .